DETERMINANTS OF AUDIT QUALITY IN THE PUBLIC SECTOR - Rahmawaty, Rahmawaty; Darwanis, Darwanis; Abdullah, Syukriy (JURNAL AKUNTANSI DAN AUDITING, 2023)
This study aims to provide a literature review on audit quality in the public sector. There are 15 articles used from 3 journal categories, namely Scopus quartile 2, international, and national indexed by Sinta 3 which were published from 2017 to 2021. This study used the Systematic Literature Review method developed by Kitchenham et al (2009). Article searches are carried out through the publish or perish application with a search focus on Scopus as the main search source. Researchers also use search sources from Google Scholar as a secondary source of supporting data. The results showed that there were 6 dominant determination factors used to measure audit quality in the 15 selected articles, namely competence, independence, professional skepticism, professional ethics, motivation, and time budget pressure.